Determinants of Liquidity Risk in the Banking System: a Systematic Literature Review - Muhammad Fikra Yafi Ulhaqqi; Noer Azam Achsani; Mohammad Iqbal Irfany (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: Post-2008, managing liquidity risk banks' ability to meet short-term obligations without major losses has become crucial. Regulatory measures like Basel III's LCR and NSFR emerged to ensure stability. With the rise of fintech, understanding liquidity determinants is increasingly relevant for stability.Purpose: This review analyzes primary determinants of liquidity risk in the banking sector, examining systematic (macroeconomic and policy-driven) and non-systematic (bank-specific) factors. It also evaluates the impact of digital banking and fintech innovations on liquidity management to inform effective risk strategies.Design/Methodology/Approach: A systematic literature review (SLR) of 30 empirical studies most relevant published from 2010 to 2024 was conducted, examining factors such as non-performing loan (financing), capital adequacy, leverage, bank size, profitability, and corporate governance. Keywords used in this study are “Liquidity and Risk” or “Management and Bank” & "Determinants" or "Factors" and "Liquidity Risk" and "Bank*” or “Banking System" or “Banking Sector*”.Finding/Result: Key liquidity risk drivers include bank size, capital buffers, macroeconomic factors, and regulatory frameworks like Basel III. Larger banks with diverse funding face lower risks, while smaller banks, especially in emerging markets, are more vulnerable. Fintech and digital banking support real-time liquidity management but raise cybersecurity concerns.Conclusion: Liquidity risk is shaped by both internal and external factors. Larger, well-capitalized banks manage it more effectively, while fintech offers new tools that require careful risk oversight. Basel III remains vital, and ESG considerations are influencing sustainable liquidity practices.Originality/value/research gap: Current research emphasizes integrating Basel III, fintech, and crisis management. Real-time tools like AI enhance liquidity management, although cybersecurity risks remain. ESG factors and the COVID-19 pandemic highlight the need for robust, sustainable liquidity frameworks. This research focuses on the role of technology advancement in liquidity risk management, which has not been widely explored in the context of emerging markets. Keywords:   bank liquidity management, basel III, emerging market, liquidity risk, technology advancement